Kualitas Layanan Access by KAI dan Kepuasan Pelanggan Mahasiswa Politeknik Negeri Bandung - Nova Andrea Ayuningtyas; Maghfira Rachma Adinda (JURNAL ADMINISTRASI KANTOR, 2024)
This study aims to analyze the effect of service quality of the Access by KAI application on customer satisfaction among Bandung State Polytechnic students. The method is descriptive quantitative with purposive sampling technique and a sample size of 107 respondents. Data was collected through a questionnaire that measures perceptions of service quality and customer satisfaction. Data analysis was performed using simple linear regression with the help of SPSS and Smart PLS. The results showed that service quality had a significant effect on customer satisfaction with a contribution of 63,5%, while 36,5% was influenced by other variables outside this study. The implication of this research is the importance of improving service quality to increase customer satisfaction and loyalty. Keywords: service quality; customer satisfaction.